LATE PERMIAN THERIODONTS (REPTILIA) FROM THE GOROKHOVETS LOCALITY (RUSSIA, VLADIMIR REGION) - Tatarinov L.P. (My University, 2004)
A new procynosuchid, Cyrbasiodon vladimiriensis sp. nov., is established on the basis of a fragmentary maxilla and an isolated postcanine from the terminal Permian of European Russia (Gorokhovets locality). The same locality yielded a dentary and a squamosal of therocephals from the family Moschowhaitsiidae.
Keywords: procynosuchid; Paleozoic::Permian; Палеозой::Пермская